Exploring Gender Stereotypes in 21st Century Philippine Narratives - CASIL-BATANG, PAULINE GRACE (International Journal of Arts, Sciences and Education, 2021)
This study examined narratives in the 21st century Philippine literature. It specifically aimed to determine whether stereotypes are present in the narratives and whether the stereotypes assigned to each gender are positive or negative. These narratives in the form of short stories were written and published within the timeframes set in this paper; 2001-2006; 2007-2012; and 2013-present and won First Prize Palanca Memorial Awards for Short Stories in English served as the corpus in this study. Mixed-method – quantitative and qualitative research design was utilized in the study where gender representations were extracted through the stereotypes assigned to male and female characters. Moreover, these stereotypes were content analyzed; they were quantified and further qualified as positive or negative stereotypes. The results show that stereotypes are present in the narratives of 21st century Philippine literature and bias is given to women for they were assigned with more negative stereotypes as compared to male characters. This presents the reality in the grassroots that despite the efforts of the government and the growing awareness of Filipinos regarding gender equality, issues related to gender still exist in the present time.